Pencantuman Batasan Tanggung Jawab Pemilik/Pengelola Situs Dalam Transaksi Jual Beli Secara Online Dan Dampaknya Bagi Konsumen - wahyudi, ari Wahyudi (UI Scholars Hub, 2015)
This paper highlights the latest developments happening in the world of law as a result of a growing trend to shop today. The trend of shopping via the internet or shopping online that supported by the development of electronic information industry and technology, in fact raises some new problems in the field of law. Sometimes one of the parties deceive or do fraud or criminal cases in the buying and selling online. Currently these cases have not been handled properly and optimally. Such circumstances can not be allowed to keep running, so as to be permissive law and violations will still occur repeatedly without giving legal certainty to be clear sanctions. Legal barren causing the person who is not acting in good intention still continue theircrimes. Anticipatory measures can be carried out by the Ministry of Trade of the Republic of Indonesia, the Financial Services Authority, the Ministry of Communications and Information Technology and the Indonesian National Police. But how about the responsibility of the shopping site administratior?